Dampak Covid-19 Terhadap Pendapatan Pedagang Kecil Di Desa Sugih Waras Kec. Teluk Gelam Kab. OKI - Nova Yanti Maleha; Imelda Saluza; Bagus Setiawan (Jurnal Ilmiah Ekonomi Islam, 2021)
This research was conducted in Sugih Waras Village, Teluk Gelam District, Ogan Komering Ilir Regency where to find out the impact of Covid-19 on the income of small traders in Sugih Waras Village, Teluk Gelam District, Ogan Komering Ilir Regency. The research method used in this research is to use a descriptive qualitative research approach. Purposive sampling technique is used by setting specific criteria that are considered representative of the population. From several interviews conducted by researchers as many as 48 samples, where the results of these interviews almost all small traders stated that during the pandemic their sales experienced a decline, especially itinerant peddler cake, basic food stalls, food stalls, coffee shops and other food stalls. where people's purchasing power decreases, their income decreases, even some of these traders experience losses from this pandemic, until their business closes or does not trade anymore. The reason for the closure of the business was due to the depletion of capital. Daily profits are used to continue the next business, some are even used to meet the daily needs of small traders. However, there were some small traders who experienced an increase in income, due to the high demand for these goods such as credit and stone sellers such as the business of selling pulses and tombstone makers experiencing a very significant increase of 60% of income before the pandemic period